The Potential of Alue Canang Village: From Natural Wealth to Local Wisdom - Umar, Muhammad Alwin Abdillah; Husna, Tasya Febriyanti; Apriliana, Ilarasati; Yani, Idar; Mawarni, Yulia; Mds , Febbyolla Anggarani; Nurcahyati; Roslaini, Roslaini (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2024)
In this KPM activity we are required to be able to practice science, technology and art. We are expected to be motivators and facilitators of development efforts, especially in rural areas that have natural wealth. One form of service that can be done is by developing the natural wealth in the village. Asset-Based Community Development (ABCD) is one approach to community development. The greatest strength in supporting the welfare of society is potential within oneself, society has been born, lived and developed so that it has assets. The expected goal is that KPM students will be able to train residents in the village in order to develop the natural wealth and local wisdom in the village. The method for implementing KPM activities is carried out in the form of outreach and training involving the community directly. One of the results that has been achieved from this KPM activity is natural wealth in the form of durian which has been developed into a traditional cake originating from Japan, namely mochi durian.